Association of the serum transaminase with mortality among the US elderly population. Issue 5 (17th March 2022) - Ke, Pan; Zhong, Lirong; Peng, Wei; Xu, Minzhi; Feng, Jie; Tian, Qingfeng; He, Yan; Dowling, Rowan; Fu, Wenning; Jiang, Heng; Zhao, Zhiguang; Lu, Kai; et al.
Abstract: Background and Aim: Considering the inconsistent findings of research into the associations between serum levels of liver enzymes (alanine aminotransferase [ALT], aspartate aminotransferase [AST], and gamma‐glutamyltransferase [GGT]) and mortality among elderly people, we aimed to investigate the associations of ALT, AST, GGT, and De‐Ritis ratio (DRR, defined as AST/ALT) and all‐cause or cause‐specific mortality among the US elderly people using National Health and Nutrition Examination Surveys data. Methods: We included 6415 elderly participants (≥ 65 years). Exclusion criteria included positive test for hepatitis B virus, hepatitis C virus, and human immunodeficiency virus infection at baseline. Multivariable‐adjusted Cox regression models calculating hazard ratios (HR) and 95% confidence intervals were developed for each of the liver enzyme measures. Results: All‐cause cumulative mortality was 33.8%, of which 23.8% were cardiovascular disease (CVD) deaths, 15.6% were cancer deaths, and 60.6% were other cause deaths. Adjusted Cox models found increased all‐cause mortality risk for low ALT (HR: 1.70), low AST (HR: 1.13), high GGT (HR: 1.25), and high DRR (HR: 1.68). Low ALT and high DRR predicted CVD mortality. Low ALT (HR: 1.91), low AST (HR: 1.16), high GGT (HR: 1.40), and high DRR (HR: 1.76) predicted other cause mortality. Conclusions: Low ALT and high DRR were associated with increased CVD and cancer mortality. All serum liver enzyme measures were associated with all‐cause mortality and other cause mortality in the US elderly population. Further studies may validate these findings in other elderly populations.